Tradisi Selapanan Sebagai Simbol Kelahiran Bayi Bagi Masyarakat Jawa - Amanda Rohmah Widyanita; Arief Sudrajat (Majalah Ilmiah Tabuah: Ta`limat, Budaya, Agama dan Humaniora, 2023)
Culture is a hereditary heritage that comes from previous ancestors, and has its own meaning and symbol based on the values ??it teaches. Culture is used as a characteristic of one group with another, where the culture is preserved as a local wisdom that can strengthen the unity and integrity of a nation. One of them is the culture originating from Java, namely the selapanan tradition. This tradition is interpreted as a traditional ceremony in welcoming a newborn baby, this is intended so that the baby gets safe later in the future and avoids interference by evil creatures that can harm him. The Javanese people hold the ceremony as the first nepton commemoration days after the baby is born. The purpose of this study is to examine more deeply the meaning of the selapanan tradition for the Javanese people and to find out the educational and religious values ??contained in the selapanan tradition for the Javanese people. The method used in this study is qualitative with descriptive analysis and is supported by literature studies from books, journals and articles. So the results obtained are the meaning of the selapanan tradition to seek safety and as a forum for socialization. Educational and religious values ??in the selapanan tradition are contained during the ceremony process, and are found in the food served to neighbors and relatives who attend.